Southern African agriculture and climate change: a comprehensive analysis - Hachigonta, Sepo; Nelson, Gerald C.; Thomas, Timothy S.; Sibanda, Lindiwe Majele (International Food Policy Research Institute, 2013)
Southern African Agriculture and Climate Change: A Comprehensive Analysis examines the food security threats facing eight of the countries that make up southern Africa — Botswana, Lesotho, Malawi, Mozambique, South Africa, Swaziland, Zambia, and Zimbabwe — and explores how climate change will increase the efforts needed to achieve sustainable food security throughout the region. Southern Africa’s population is expected to grow at least through mid-century. The region will also see income growth. Both will put increased pressure on the natural resources needed to produce food, and climate change makes the challenges greater. Southern Africa is already experiencing rising temperatures, shifting precipitation patterns, and increasing extreme events. Without attention to adaptation, the poor will suffer.